Return and volatility spillover eﬀects: Evaluating the impact of Shanghai and Shenzhen-Hongkong Stock Connect Programs on A-H-US stock markets ---An empirical analysis based on VAR-GARCH model - JI, BAIHAO (2019)
This paper estimates the change of return and volatility spillover effects on stock markets in the Chinese mainland, U.S. and Hong Kong before and after stock connect programs and also analyse the dynamic interrelationships among them for the risk diversification and portfolio management over the global capital markets in the background of financial liberalisation. The different point of this paper compared with previous studies is that this research firstly considers the three stock markets simultaneously based on the implement of the particular financial reform system. The VAR model and GJR GARCH model are introduced in this study to explore return and volatility spillover effects among the Chinese mainland, the U.S. and Hong Kong stock markets. The BEKK GARCH model perfects the research about volatility spillover effect as well as illustrate the bidirectional information transmission mechanism by the lagged value of each market for itself or cross markets. This finding indicated that the Chinese mainland stock market transferred its position from a receiver of market risk to a leader and sender when considering its bilateral relationship with Hong Kong stock market through the building of both stock markets connect programs. Although American stock markets still occupy the leading position in the global capital market and exert its influence on the Chinese mainland and Hong Kong, while this effect for stock markets in the Chinese mainland is diminishing. The empirical result might provide useful information and guideline for international and domestic capital which concern the risk diversification and co-movement over the global capital markets. The limitation of this study shall be paid more attention to revolve it in further study in the future.